Cholinergic Modulation of Cortical Microcircuits Is Layer-Specific: Evidence from Rodent, Monkey and Human Brain - Obermayer, Joshua; Verhoog, Matthijs B.; Luchicchi, Antonio; Mansvelder, Huibert D. (Frontiers in Neural Circuits, 2017)
Acetylcholine (ACh) signaling shapes neuronal circuit development and underlies specific aspects of cognitive functions and behaviors, including attention, learning, memory and motivation. During behaviour, activation of muscarinic and nicotinic acetylcholine receptors (mAChRs and nAChRs) by ACh alters the activation state of neurons, and neuronal circuits most likely process information differently with elevated levels of ACh. In several brain regions, ACh has been shown to alter synaptic strength as well. By changing the rules for synaptic plasticity, ACh can have prolonged effects on and rearrange connectivity between neurons that outlasts its presence. From recent discoveries in the mouse, rat, monkey and human brain, a picture emerges in which the basal forebrain (BF) cholinergic system targets the neocortex with much more spatial and temporal detail than previously considered. Fast cholinergic synapses acting on a millisecond time scale are abundant in the mammalian cerebral cortex, and provide BF cholinergic neurons with the possibility to rapidly alter information flow in cortical microcircuits. Finally, recent studies have outlined novel mechanisms of how cholinergic projections from the basal forebrain affect synaptic strength in several brain areas of the rodent brain, with behavioural consequences. This review highlights these exciting developments and discusses how these findings translate to human brain circuitries.